Retrobulbar circulation in myopic patients with or without myopic choroidal neovascularisation. Issue 7 (1st July 2002) - Dimitrova, G; Tamaki, Y; Kato, S; Nagahara, M
Abstract : Aim: To investigate the effect of myopia and myopic choroidal neovascularisation (CNV) on retrobulbar circulation in central retinal artery (CRA) and vein (CRV) and posterior ciliary artery (PCA). Methods: 52 subjects with and without myopia were included in the study. Retrobulbar circulation was measured using colour Doppler imaging. Analysis of correlation of degree of myopia with blood flow velocity parameters was done. Circulatory differences between eyes of patients with unilateral neovascular degenerative myopia were estimated. Results: The analysis of correlation between dioptry and blood flow velocity in the CRA, CRV, and PCA showed a significant positive correlation. Axial length was also significantly correlated with CRA and CRV blood velocity and had a tendency to be correlated with PCA blood velocity. When compared with the fellow eye, the eye with myopic CNV had significantly higher resistivity index (RI) (p=0.048) in the PCA and no significant difference in the circulatory parameters of the CRA and CRV. Conclusion: Central retinal and posterior ciliary blood velocity decreases with the increase of the degree of myopia. PCA RI is higher in myopic CNV.